ANALISIS PENGAWASAN DAN KINERJA APARATUR PEMERINTAH DAERAH - Rifai Yusuf (Universitas Swadaya Gunung Jati, 2013)
Implementation of the monitoring task in today's society is a beacon of hope , if we review the history of surveillance in our country since we carry out the development plan that we are familiar with the Five-Year Plan , it has since we also began to implement the basics of administrative management in the absence of planning seklus , implementation , monitoring , thus the three elements of management is an integral and equal weight , that can be attributed to the prinsifnya supervision is very important . In the implementation of regional autonomy kelacaran pegawasan in local government organization is necessary for the organization of local governments to work effectively and efficiently and economically , as well as supervision is one important element in order to improve the performance of araturur in performing common tasks and building a clean government and authoritative therefore deemed necessary to improve the implementation of effective monitoring body within the apparatus of government in each of continuous and thorough . through supervision fungisonal to establish the level of success of governance and implementation of development one of them held a performance assessment of local government officials over menfaat and successful policies, implementation of programs , projects and activities . Konci words : monitoring , performance of local government officials